A Delicate Nanoscale Motor Made by Nature—The Bacterial Flagellar Motor. Issue 9 (25th June 2015) - Xue, Ruidong; Ma, Qi; Baker, Matthew A. B.; Bai, Fan
<x xml:space="preserve">Abstract</x> The bacterial flagellar motor (BFM) is a molecular complex ca. 45 nm in diameter that rotates the propeller that makes nearly all bacteria swim. The motor self‐assembles out of ca. 20 different proteins and can not only rotate at up to 50 000 rpm, but can also switch rotational direction in milliseconds and navigate its environment to maneuver, on average, towards regions of greater benefit. The BFM is a pinnacle of evolution that informs and inspires the design of novel nanotechnology in the new era of synthetic biology.